Relationships between Color and Some Properties in Red-Reddish and Neighbour Soils in Isparta, Turkey - Akgul, Mesut; Ali Isildar, A.; Basayigit, Levent (Asian Journal of Chemistry, 2016)
Relationships between soil colour and some selected properties of eighty soil samples were investigated. The samples were collected from surface and subsurface horizons and/or layers of red-reddish coloured soils and neighbour soils located in Isparta, Turkey. Soil samples were analyzed for lime, organic matter, free iron oxide, soil reaction, cation exchange capacity, and particle size distribution. In addition, colour parameters (hue, value and chroma) and redness rating of soil samples were also determined. The dominant hues on more stable older geomorphic surfaces and more oxidized drainage conditions are 2.5 and 5 YR. While 7.5 YR is dominant on surfaces related to erosion and transportation, 10 YR generally is observed on examination of all landscape positions and all drainage conditions. It was found that there were significant differences for redness rating, free iron oxide and lime contents of soils that have different hue. Meaningful differences were not obtained for cation exchange capacity, organic matter, clay, silt and sand contents of soils. In addition to these results, the significant correlation coefficients were obtained to be 0.76 between redness rating and free iron oxide, to be 0.68 between hue and free iron oxide, to be 0.68 between lime and dry value.